Analisis Manajemen Dakwah melalui Media Digitalisasi Maulid Arbain Studi Kasus Majelis Taklim Darusshofa Medan - Efendi, Erwan; Soraya, Siti Fitria; Hajar, Siti; Mughayyir, Ahmad Arib; Alazizi, Osama (IAI Nasional Laa Roiba Bogor, 2023)
Da'wah is an everyday phenomenon of practicing Islamic teachings delivered by a da'i which can be enjoyed by the Islamic community in Indonesia. The era of digitalization should be a momentum as an opportunity and challenge to realize Islamic da'wah that can run effectively and efficiently. The aim of this research is to describe the da'wah media in the management of the Darusshofa Taklim Council as a religious education community in the city of Medan. This method uses a qualitative field research type approach with interview techniques, observation, through staff members of the Medan Taklim Darusshofa Council. MT Darusshofa channel staff, several da'wah media used by this taklim assembly such as YouTube, Facebook, and Instagram, FB with the name Darusshofa Medan Taklim Assembly, Instagram with the name Darusshofa Medan and YouTube channel with the name DSTV. Live broadcast using VMIX and will be broadcast or uploaded on DSTV media. Solutions related to unclear sound MT also provides sound at the Arbain birthday to avoid damage during the event and the need for good communication related to the management of Arbain facilities so that these activities run smoothly.